Functionalized Natural Particles: Light‐Induced Surface Modification of Natural Plant Microparticles: Toward Colloidal Science and Cellular Adhesion Applications (Adv. Funct. Mater. 18/2018). (2nd May 2018) - Tan, Ee‐Lin; Potroz, Michael G.; Ferracci, Gaia; Jackman, Joshua A.; Jung, Haram; Wang, Lili; Cho, Nam‐Joon
Abstract : Light‐based surface modification of discrete pollen microparticles extracted from bee‐collected pollen agglomerates highlights the potential of pollen in colloidal science. As demonstrated by Nam‐Joon Cho and co‐workers in article number1707568, ultraviolet light/ozone treatment of pollen increases surface atomic oxygen in the form of ketone bonds. This improves pollen wetting, the ability to tune microparticle‐stabilized Pickering emulsions, and increases cell/pollen binding.